The Concept of Medical Errors, Adverse Events and Iatrogenic Disease - Terminological Consideration - Korytkowska, Daria (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article is the short analysis of the selected foreign literature created in terms of the connection between concepts like medical error, adverse event and the iatrogenic disease. These terms are often used interchangeably therefore it becomes essential to identify the differences that exist between them in order to eliminate the possible errors in interpretation. The author also attempts to draw attention to the large number of publications produced every year that talk about those terms. This, on the other hand, is supposed to confirm their (the terms) relevance, what the various groups of the doctors, lawyers, ethicists, insurance companies and many others raise.